Analysis of Just In Time Implementation as an Effort to Increase Production Efficiency in the Plywood Industry - Azizah, Fitrotul; Nusantara, Ari Fahimatussyam Putra (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The study aims to determine the application of just-in-time in plywood production and to determine the indicators of just-in-time success in increasing the efficiency of plywood production at PT. Cendana Putra Nusantara Tegalsiwalan-Probolinggo. The methodology used in this study is a qualitative approach with a descriptive type. Data collection techniques include observation, interviews, and documentation. This study shows that PT. Cendana Putra Nusantara applies the just-in-time method by eliminating waste that does not add value to the product, such as overproduction, waiting time, inventory, transportation, processing, motion, or production defects, although it is still not optimal. Furthermore, the application of the just-in-time method at PT. Cendana Putra Nusantara, although not yet fully maximized, can increase the company's production efficiency with the level of capacity utilization, level of labor utilization, level of raw material utilization, level of order completion, service, and level of errors or defects. Keywords: Management Accounting; Just-in-time; Production Efficiency; Manufacturing Company; Plywood